Nitrophenoxy groups containing polybenzimidazoles as polymer electrolytes for fuel cells: synthesis and characterization - Kulkarni, Mahesh; Potrekar, Ravindra; Kulkarni, R. A.; Vernekar, S. P. (Journal of Applied Polymer Science, 2010)
Polybenzimidazoles containing different contents of pendant nitrophenoxy groups were prepared by condensation of 3,3'-diamino-benzidine with a mixture of 3,5-dicarboxyl-4'-nitro diphenyl ether and isophthalic acid (IPA) in different ratios in polyphosphoric acid. The polymers are soluble in polar aprotic solvents, they have inherent viscosities in the range of 0.75-1.10 dL g(-1) and they form tough and transparent films on solution casting. They have good thermal stability with initial decomposition temperature ranging from 380 to 416 degrees C in nitrogen, good tensile strength ranging from 56 to 65 MPa and reasonably good oxidative stability. Phosphoric acid uptake of these polymers is low compared with PBI and membranes doped with phosphoric acid exhibit good proton conductivity in the range of 6.6x 10(-3) to 1.9x 10(-2) S/cm at 25 degrees C and 1.2x 10(-2) to 4.9x 10(-2) S/cm at 175 degrees C, compared with 3.9x 10(-3) S/cm at 25 degrees C and 3.2x 10(-2) S/cm at 175 degrees C for PBI. These membranes are suitable for applications as polymer electrolyte for fuel cell and presumably for gas separation at high temperature. (C) 2010 Wiley Periodicals, Inc. J Appl Polym Sci 117: 3282-3292, 2010
Keywords: Characterization; membranes; pendant nitrophenoxy group; polybenzimidazoles; proton conductivity; synthesis

Proton-conducting supramolecular metallogels from the lowest molecular weight assembler ligand: a quote for simplicity - Saha, Subhadeep; Schoen, Eva-Maria; Cativiela, Carlos; Diaz, David Diaz; Banerjee, Rahul (Chemistry-A European Journal, 2013)
Oxalic acid has been proven to be the lowest molecular weight organic ligand able to form robust supramolecular metallogel networks in the presence of metal salts. In particular, two novel multifunctional metallogels were readily prepared at room temperature by simple mixing of stock solutions of Cu-II acetate monohydrate or Cu-II perchlorate hexahydrate and oxalic acid dihydrate. Formation of different polymorphs and unprecedented proton conduction under anhydrous conditions were also demonstrated with some of these materials.
Keywords: Copper; low-molecular-weight ligands; metallogels; proton conductivity; supramolecular chemistry

Studies on nano composites of SPEEK/ethylene glycol/cellulose nanocrystals as promising proton exchange membranes - Bano, Saleheen; Negi, Yuvraj S.; Illathvalappil, Rajith; Kurungot, Sreekumar; Ramya, K. (Electrochimica Acta, 2019)
The present work deals with fabrication and characterisations of nano-composite membranes composed of sulfonated poly (ether ether ketone) (SPEEK) cross-linked and reinforced with ethylene glycol (EG) and cellulose nanocrystals (CNCs) respectively. The thin films of cross-linked composite membranes were prepared by solvent casting method and further analysed for physicochemical and electrochemical properties to execute their applicability as promising proton exchange membrane (PEM) in fuel cells. The process of cross-linking helps to improve the strength and dimensional stability of bare SPEEK membranes without compromising with conductivity. However, presence of CNCs further improves the strength and provides an effective pathway for the conduction of protons in membranes by interacting through their surface hydroxyl and sulfonic acid groups with ionic moieties of polymer matrix. All prepared composite membranes showed good oxidative and thermal stability along with good proton conductivity. The cross-linked SPEEK membranes with 4 wt% loading of CNCs possess an appreciable proton conductivity of 0.186 S/cm at 95 degrees C and 95% RH which is comparable to Nafion 117. From the view point of above studies, the prepared nano-composite can be described as promising proton exchange membrane for fuel cells. (c) 2018 Elsevier Ltd. All rights reserved.
Keywords: Cellulose nanocrystals; Cross-linked SPEEK; fuel cell; oxidative stability; proton conductivity

Functionalized single-walled carbon nanohorns to reinforce sulfonated poly(ether ether ketone) electrolyte for direct methanol fuel cells - Turanelloormana, Parameswaran; Sarmah, Sudeshna; Torris, Arun; Bhat, Santoshkumar D.; Unni, SreeKuttan M. (ChemElectroChem, 2020)
Carbon-nanomaterial-based additives are promising materials for improving the physicochemical properties of sulfonated polyether ether ketone (sPEEK) for its use as composite membrane electrolyte in direct methanol fuel cells (DMFCs). In this work, functionalized single-wall carbon nanohorns (f-SWNHs) are realized as an additive in sPEEK. The -COOH groups created on the SWNHs during peroxide treatment improve the dispersion of f-SWNHs in sPEEK and boost the proton conductivity, ion exchange capacity, mechanical properties and reduce the methanol permeability of the electrolyte. The composite membrane with 0.50 wt.% f-SWNHs shows improved electrochemical selectivity of 17.03x10(-4) Scm(-3)s and delivers the highest peak power density of 230 mW cm(-2)in DMFCs.
Keywords: carbon nanohorns; direct methanol fuel cells; membrane electrolyte; proton conductivity; sulfonated poly ether ether ketone

Chemically gradient hydrogen-bonded organic framework crystal film - Mohammed, Abdul Khayum; Raya, Jesus; Pandikassala, Ajmal; Addicoat, Matthew A.; Gaber, Safa; Aslam, Mohamed; Ali, Liaqat; Kurungot, Sreekumar; Shetty, Dinesh (Angewandte Chemie-International Edition, 2023)
Hydrogen-bonded organic frameworks (HOFs) are ordered supramolecular solid structures, however, nothing much explored as centimetre-scale self-standing films. The fabrication of such crystals comprising self-supported films is challenging due to the limited flexibility and interaction of the crystals, and therefore studies on two-dimensional macrostructures of HOFs are limited to external supports. Herein, we introduce a novel chemical gradient strategy to fabricate a crystal-deposited HOF film on an in situ-formed covalent organic polymer film (Tam-Bdca-CGHOF). The fabricated film showed versatility in chemical bonding along its thickness from covalent to hydrogen-bonded network. The kinetic-controlled Tam-Bdca-CGHOF showed enhanced proton conductivity (8.3x10(-5) S cm(-1)) compared to its rapid kinetic analogue, Tam-Bdca-COP (2.1x10(-5) S cm(-1)), which signifies the advantage of bonding-engineering in the same system.
Keywords: Chemical Gradience; Crystal Films; Free-Standing Films; hydrogen-bonded organic framework; Interfacial Chemistry; proton conductivity

Unlocking the potential of proton conductivity in guanidinium-based ionic covalent organic nanosheets (iCONs) through pore interior functionalization - Kumar, Sushil; Hu, Jiahui; Pandikassala, Ajmal; Kurungot, Sreekumar; Addicoat, Matthew A.; Szekely, Gyorgy (Applied Materials Today, 2023)
Recently, scientists have been exploring the incorporation of proton carriers such as water and phosphoric acid (PA) into the pores and channels of porous materials to enhance proton conduction performance. Ionic covalent organic nanosheets (iCONs) have been identified as promising functional materials due to their inbuilt ionic interfaces, which can facilitate strong interaction with counter ions present inside the pore structure and thus shorten ion transport pathways. However, there is a lack of research related to proton conductivity in iCONs loaded with PA. To address this, we prepared three functionalized guanidinium-based iCONs using a solvothermal condensation reaction between guanidinium amine (TG) and functionalized terephthaldehyde (Da, Dha, and Dma). PA was also incorporated into the iCON structure via ex situ loading to observe its effects on proton conduction performance. The results showed that both the iCONs and PA-iCONs were highly stable in water, organic solvents, acidic and basic media. Amongst these PA-iCONs, one with hydroxyl-functionalization (PA-DhaTG) displayed high proton conductivity at 90 degrees C and 95% relative humidity due to a Grotthuss mechanism for protons. These functionalized guanidinium-based iCONs could prove useful for applications in energy conversion devices.
Keywords: chemical stability; Functionalized pore interior; Guanidinium group; ionic covalent organic nanosheets; proton conductivity